The potential of Epimedium koreanum Nakai for herb–drug interaction. (27th June 2017) - Zhong, Qingxiang; Shi, Ziqi; Zhang, Li; Zhong, Rongling; Xia, Zhi; Wang, Jing; Wu, Hao; Jiang, Yutong; Sun, E.; Wei, Yingjie; Feng, Liang; Zhang, Zhenhai; et al.
Abstract: Objectives: This study aims to investigate potential herb–drug interactions (HDI) of Epimedium koreanum Nakai. Methods: Human liver microsomes (HLMs) were used to determine the enzyme kinetics of the major human cytochrome P450s (CYPs). Inducible potential of E. koreanum on CYP1A2, 2B6, 2C19 and 3A4 activities of human primary hepatocytes was also examined. Key findings: Ethanol extract of E. koreanum showed direct inhibitory potency for CYP1A2 (IC50  = 121.8 μg/ml, K i  = 110.7 ± 36.8 μg/ml) and CYP2B6 (IC50  = 59.5 μg/ml, K i  = 18.1 ± 2.9 μg/ml). For CYP2C9, 2C19, 2D6, 2E1 and 3A4, only negligible effect was observed. Time‐dependent (irreversible) inhibition by E. koreanum was observed for CYP1A2 ( K I  = 32.9 ± 18.4 μg/ml, k inact  = 0.031 ± 0.006 min −1 ). However, ethanol extract of E. koreanum (1.5–150 μg/ml) did not change the activity or mRNA expressions for CYP3A4, 1A2, 2C19 and 2B6. Conclusions: The ethanol extract of E. koreanum is not likely to cause HDI via inducing the major human CYPs. But the potential for interactions between E. koreanum extract and substrates of CYP1A2 or 2B6 cannot be overlooked.